Retinal vessel oxygen saturation and vessel diameter in retinitis pigmentosa at various ages - Zong, Yao; Lin, Leilei; Yi, Changxian; Huang, Xia; Fu, Yue; Dong, Yanmin; Qian, Xiaobing; Li, Yujie; Gao, Qianying (Graefe's archive for clinical and experimental ophthalmology, 2016)
Purpose This study was conducted to determine whether oxygen saturation and retinal blood vessel diameter are affected by retinitis pigmentosa (RP) at various ages. Methods Relative oxygen saturation was measured in retinal blood vessels in 68 RP patients and 136 normal subjects using the Oxymap T1 retinal oximeter. Subjects were divided into two age groups: Group A (20–40 years) and Group B (> 40 years). One randomly selected eye of each subject was used for statistical analysis. Student's t tests were used to analyze the mean saturation and diameter of retinal arterioles and venules and arteriovenous differences between RP and normal subjects in the two age groups. A Spearman test was used to analyze the correlation of mean saturation of retinal arterioles (AS) and arteriovenous differences (AVS) with visual acuity, disease duration, and electroretinogram (ERG) b-wave amplitude in patients with RP. Results AS was significantly higher in patients with RP (105.5 ± 9.4 %) than in normal subjects (94.5 ± 4.4 %, p = 0.000) in Group A, while in Group B, AS was significantly lower in RP patients (86.8 ± 10.3 %) than in healthy subjects (96.0 ± 4.8 %, p = 0.000). Vessel diameter was smaller in RP patients than in normal subjects. AS and AVS showed a negative correlation with disease duration and a tendency toward positive correlation with ERG b-wave in patients with RP. Conclusions The shifting characteristics of retinal vessel oxygen saturation suggest that the pathological mechanism of retinal oxygen metabolic disorder differs by age in patients with RP.